Influence of alfalfa addition to sow diets - D S Pollmann; S M Dennis; R R LaForge (Kansas Agricultural Experiment Station Research Reports, 1983)
Twenty-four sows were utilized to evaluate the influence of a high fiber diet on nutrient digestibility and hindgut bacterial populations and volatile fatty acid (VFA) concentrations. Sows were fed either a control of milo-soybean meal or a 50% sun-cured alfalfa diet. The addition of alfalfa decreased (P<.05) energy, nitrogen and fiber utilization as compared to the control diet. Alfalfa-fed sows, after a 90-day adaptation, were able to utilize more cellulose and crude fiber, which contributed to slight improvement in energy utilization. Bacterial populations and VFA concentrations in the hindgut were altered when sows were fed a 50% alfalfa diet. Therefore, these results indicate that alfalfa, if cost effective, can be added to sow diets.; Swine Day, Manhattan, KS, November 10, 1983
Keywords: Swine day; 1983; Kansas Agricultural Experiment Station contribution; no. 84-174-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 442; Swine; Alfalfa; Sow; Diet